Outcomes of renal transplant from donors with polycystic kidney disease. (March 2018) - Shamali, Awad; Milsom-Mcquillan, Sarah; Gibbs, Paul
Abstract: Introduction: Kidneys from donors affected by autosomal-dominant polycystic kidney disease (ADPKD) are, in general, considered unsuitable for transplantation. However, some authors report cases of patients who received kidneys from a deceased ADPKD donor showing encouraging outcomes. Our aim is to provide our experience of a patient with end stage renal failure who received a deceased donor kidney from a 29-year-old who themselves had been diagnosed with ADPKD but well maintained renal function, and to provide a comprehensive review of all the published literature. Methods: In addition to our case, a literature search (PubMed database, Embase, Cochrane Library) of articles published between 1980 and 2017 was performed. Results: Sixteen cases were identified. Median donor age was 24 (range12–55) years old. Median recipient age was 46 (range 19–72) years old. Fifteen cases had a single kidney transplant and one case had a dual kidney transplant. 13/16 (81%) had immediate function, 2 patients (12.5%) had delayed graft function and one patient (6.25%) had primary non-function. Median graft follow up was 36 months (range 6–180). Median serum creatinine at last follow up was 124 μmol/L (range75–442). Thirteen patients (81%) were still alive with a working renal transplant at last follow up. Conclusion: The published literature is encouraging and supports the use of polycystic kidneys from younger deceased donors. Therefore, we believe that if kidneys from ADPKD donors are offered, they should have a full assessment and be considered acceptable for renal donation to recipients who may have a life expectancy of 10 years or less and who are fully informed and have the capacity to consent to receiving a polycystic kidney. Highlights: Good results of kidney transplants from ADPKD donors. ADPKD should be considered as a marginal donors in kidney transplant. ADPKD donors should be considered for appropriate recipients.